Związek Patriotów Polskich jako organizator repatriacji obywateli polskich z ZSRR w latach 1945–1946 - Marciniak, Wojciech Franciszek (Pamięć i Sprawiedliwość, 2014)
The Polish-Soviet agreement on option and repatriation concluded in Mos- cow on 6 July 1945 allowed Polish citizens in exile in the Soviet Union to return to their homeland. However, shortly after the signing of the agreement, it turned out that most of those concerned did not meet the conditions imposed by the Soviet authorities and could not exercise their right to repatriation. The unfavourable interpretation of the agreement provisions by the Soviets meant that it was essentially an invalid document. Only the diplomatic intervention of Professor Henryk Raabe, Polish Ambassador in the Soviet Union, made the prospect of repatriation became real again. The repatriation operation was overseen by the Union of Polish Patriots (ZPP). Field units of the organisation were involved in the procedure of changing the nationality of the exiles, carried out an informational campaign, gathered stocks of clothing, food and medicine for the journey, cooperated with railway authorities in clearing transports, etc. The resettlement of over a quarter of a million people from vast areas of Russia, Siberia and Central Asia was an extremely difficult and demanding operation which required proceeding in accordance with a specific plan. The responsible units of ZPP began preparations for the repatriation already in September 1945. The first transports of our compatriots to Poland departed as late as in February next year. The operation ended in June 1946. For the employees and activists of ZPP, as well as the exiles, these ten months meant increased organisational effort. Owing to the efforts of the Union of Polish Patriots, approximately 250,000 Polish citizens – exiles of the years of war and Soviet occupation – safely returned to their homeland in a well-organised operation.